2017
DOI: 10.24926/iip.v8i4.935
|View full text |Cite
|
Sign up to set email alerts
|

Using Debates to Mimic Clinical Discussion in Experiential Education

Abstract: Critical thinking and application of knowledge to an ambiguous patient care scenario are often difficult skills to cultivate in learners. Use of traditional teaching techniques (e.g. topic discussions and journal clubs) helps to develop these competencies within learners. However, alternative teaching strategies may help develop critical thinking and direct application. Debates have been used in healthcare education for decades with positive results. This paper provides supporting evidence for use of debates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…Through such activities, the students' critical thinking is promoted. The skill of oral communication in this study is promoted by debates as reported in some previous studies (Hall, 2011;Hartin, 2017;Mumtaz & Latif, 2017;Nisly et al, 2017;Shaw, 2012;Zare & Othman, 2015). The skill of effective communication represents the heart of quality healthcare (Ralph & Moloney, 2015), affecting the success of the outcome of nursing care for patients (Kourkouta & Papathanasiou, 2014).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Through such activities, the students' critical thinking is promoted. The skill of oral communication in this study is promoted by debates as reported in some previous studies (Hall, 2011;Hartin, 2017;Mumtaz & Latif, 2017;Nisly et al, 2017;Shaw, 2012;Zare & Othman, 2015). The skill of effective communication represents the heart of quality healthcare (Ralph & Moloney, 2015), affecting the success of the outcome of nursing care for patients (Kourkouta & Papathanasiou, 2014).…”
Section: Discussionmentioning
confidence: 77%
“…Research shows that debates are a pedagogical method that can be applied to promote critical thinking and oral communication skills among students (Doody & Condon, 2012;Hartin, Birks, Bodak, Woods, & Hitchins, 2017). Debates foster self-directed learning, participation in a shared dialogue, and teamwork (Nisly, Kingdon, Janzen, & Dy-Boarman, 2017). Debates allow students to develop knowledge of substantive topics and exercise skills through practice activities (Doody & Condon, 2012;Hartin et al, 2017) and offer the participants the ability to explore a topic in more than one correct stance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Debates require the exercise of logic, critical thinking skills, clear spontaneous communication, increased breadth of evaluated literature, and a more robust and engaging educational value for attendees. [8][9][10] Students must demonstrate that they can analyze and synthesize literature to argue their position, refute the opposition when necessary and apply data to real life scenarios. Thus, a debate more closely reflects the problem solving skills that are necessary for clinical decision-making during direct patient encounters and collaborative discussions with team members.…”
Section: Introductionmentioning
confidence: 99%